2021
DOI: 10.1097/md.0000000000026616
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcomes of self-expandable metal stent treatment for malignant colorectal obstruction

Abstract: There has been increased use of self-expandable metal stents (SEMS) in treating malignant colorectal obstruction (MCO). The aim of this study was to investigate factors that are associated with the outcomes of SEMS placement for MCO. Clinical data from patients who underwent SEMS placement for MCO at 6 hospitals in Honam province of South Korea between 2009 and 2018 were reviewed retrospectively. Eight hundred two patients were identified and their data were analyzed. Technical success, clinical suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Studies have reported the association of advanced stages and peritoneal carcinomatosis with clinical outcomes. [27,28] However, to our knowledge, no previous studies have investigated the association between the T stage and clinical outcomes of stent insertion in MCO. A possible reason for this result is that the deeper infiltration of the tumor may lead to the fixation of the bowel, leading to decreased peristalsis and limitation of stent expansion after placement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the association of advanced stages and peritoneal carcinomatosis with clinical outcomes. [27,28] However, to our knowledge, no previous studies have investigated the association between the T stage and clinical outcomes of stent insertion in MCO. A possible reason for this result is that the deeper infiltration of the tumor may lead to the fixation of the bowel, leading to decreased peristalsis and limitation of stent expansion after placement.…”
Section: Discussionmentioning
confidence: 99%